The Main Drivers of Environmentally Responsible Behaviour in Lithuanian Households - Dalia Streimikiene (Amfiteatru Economic Journal, 2015)
Preserving environmental and natural resources is one of the most important challenges for ensuring the sustainability of well-being over time. One can notice that measuring of environmental indicators related to environmentally responsible behaviour is complicated and demanding task. It is also important to define the main drivers of environmentally responsible development. The objective of this paper is to provide comparatives analysis of indicators of environmentally responsible behaviour in the Baltic States by comparing and assessing them in terms of the EU-28 average and to present the main drivers of environmentally responsible behaviour in Lithuania. Environmentally responsible behaviour is related to resource and energy savings, use of renewable energy sources, waste sorting and recycling, wastewater disposal etc. Comparative assessment of environmentally responsible behaviour indicators in the Baltic States indicated that all these indicators are bellow the EU-average, except the use of renewable energy sources. The main drivers of consumption behaviour in Lithuania were assessed by applying households surveys in order to define the major issues of concern and to develop relevant policies targeting these issues. Age, gender, education, and income of Lithuanian residents do not have impact on environmentally responsible behaviour in Lithuanian households (energy saving, buying energy efficient electric appliances, willingness to pay electricity from renewable energy sources use of biofuels). Only environmental awareness has impact on energy saving behaviour at home and use of biofuels in cars and waste recycle.
Keywords: Q41; Q5; Q58; C91; 330; environmentally responsible behaviour; drivers of behavioural changes; resource productivity; energy productivity; renewable energy sources; waste recycling